2007
DOI: 10.1080/09500340600855122
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for separating the components of the clinical electroretinogram

Abstract: Ganzfeld electroretinograms (ERG) are summated responses of various layers of the retina to a flash of light. Pharmacological and non-invasive techniques are used in research labs to separate out the components arising from these layers. These methods, however, cannot be applied to ERG obtained in clinics for diagnostic purposes. Here, we outline the applicability of wavelet techniques to separate a-wave, b-wave and at least one oscillatory potential (OP) from the ERG obtained under scotopic conditions. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Review of the literature showed that several mother wavelets have been applied in DWT of the ERG response, such as the “Daubechies” wavelets [ 20 , 21 , 25 ], the “Haar” wavelet [ 24 , 35 ] and the “Mexican hat” [ 23 , 36 , 37 ]. For glaucoma, Miguel-Jiménez et al have successfully applied DWT to the global flash mfERG response in advanced glaucoma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the literature showed that several mother wavelets have been applied in DWT of the ERG response, such as the “Daubechies” wavelets [ 20 , 21 , 25 ], the “Haar” wavelet [ 24 , 35 ] and the “Mexican hat” [ 23 , 36 , 37 ]. For glaucoma, Miguel-Jiménez et al have successfully applied DWT to the global flash mfERG response in advanced glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…Its use has been increasingly studied and applied either to improve the interpretation of the biosignal itself (ECG [ 17 ], EMG [ 18 ]) or to exclude interference between signals [ 19 ]. In electrophysiology of vision, this method has been introduced a decade ago [ 20 , 21 ]. It has been used to analyze the photopic negative response in the full-field ERG of healthy subjects [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, wavelet techniques have been applied in electrophysiology to separate the components of the clinical ERG (Varadharajan et al 2007) and to analyze the dynamics of the oscillatory potentials in the rat retinal response (Forte et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DWT coefficients were shown to be superior to traditional TD measures in segregating normal and pathological PERG waveforms using principal components analysis (Rogala & Brykalski, 2005). It was also shown that it is possible to approximate the TD a-wave, b-wave, and at least one OP using the inverse DWT of the scotopic ERG waveform (Varadharajan, Fitzgerald, & Lakshminarayanan, 2007). Similarly, Miguel-Jiménez, Boquete, Ortega, Rodriguez-Ascariz, and Blanco (2010) used the DWT decomposition to reconstruct mfERG waveforms into different frequency bands and suggested that this approach could potentially be more sensitive to detect changes in glaucoma patients, compared to Humphrey visual field tests.…”
Section: Introductionmentioning
confidence: 99%